Children of intercountry adoptions in school : a primer for parents and professionals - Meese, Ruth Lyn (Bergin & Garvey, 2002)
Offers practical guidelines and suggestions for parents and school personnel to better understand and meet the educational needs of the children of intercountry adoption. Children of intercountry adoption have complex histories that place them at high risk for difficulty or failure in school. Teachers and other school professionals often do not know how to test them, teach them, or meet their needs. This volume explains those needs and offers guidelines and suggestions to maximize the educational performance of these children and help them meet their potential. The volume includes research following children adopted from several countries, including Russia and former Soviet states, Romania, and China. Information from adoption literature on English as a Second Language classes, as well as special education law and research is presented. In addition, the volume offers stories of real children adopted from Romania, Russia, and China, their parents, and their interactions with schools in the United States.